Application and Discussion of Intelligent Operation and Maintenance of BIM Visualization Platform for Drainage Pumping Stations - PENG Muzhan; ZANG Peiyuan; REN Weixu; GAO Ting; XU Zedian (Renmin Zhujiang)
The construction of a BIM visualization platform for the intelligent operation and maintenance of drainage pumping stations is an important part of smart water.It plays a crucial role in improving the project management level,reducing the loss of possible flood disasters,and strengthening the ability of water utilities to deal with risks.However,in the operation and maintenance management of traditional water utilities,the backward management methods and means often result in problems such as high costs,low efficiency,and slow response.Therefore,this paper puts forward a solution to the top-level design of the platform architecture.In view of the current management practice,we realize the functions including BIM model visualization,the unit operation status display,inventory asset management,statistical report query,and personnel management by combining the platform with the emerging technologies in the information field.This study demonstrates a good engineering application for the construction of the intelligent operation and maintenance platform and can be used for reference for the follow-up construction of smart water and the informatization of water conservancy.